Influence of the previous state of corrosion of rebars in predicting the service life of reinforced concrete structures. (10th November 2018) - Martinez-Echevarria, M.J.; Lopez-Alonso, M.; Cantero Romero, D.; Rodríguez Montero, J.
Highlights: Consequences of pre-rusting in reinforced concrete. Remarks about service-life of reinforced concrete structures. Evolution of corrosion steel by electrochemical methods. Abstract: Before being imbedded in concrete, rebars often contain rust layers. It is uncertain whether these layers may affect the stability required for the steel in reinforced concrete (RC) structures, as there is a lack of scientific consensus in the limited research dedicated to evaluating such an influence. The present paper therefore describes an experimental study aimed to clarify the consequences of rebar pre-rusting in the service life of RC structures. Samples of corroded reinforcement in construction works underway were collected and characterized, then embedded in concrete blocks. The evolution of their behavior was followed by measuring their corrosion rate. The results obtained show that the corrosion rates of the pre-rusted rebars were greater than those of the rebars that had not undergone any type of previous moisture-related corrosion. Under such circumstances the Tuutti "initiation period" would have disappeared, meaning its service life could be reduced to unacceptable values.